2017
DOI: 10.1159/000487052
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Genotype 1a and 1f of Hepatitis E Virus in Patients Treated at Tertiary Care Hospitals in Central India

Abstract: Background and Aims: An acute hepatitis, caused by hepatitis E virus (HEV), is a significant global health concern, especially in developing countries. HEV has 1 serotype and 8 genotypes, which are further divided into subtypes. Despite the availability of sporadic cases and outbreak data from India, specific information regarding HEV epidemiological data is lacking from central India. This study was conducted to understand epidemiological and molecular features of HEV in central India. Methods: In this 3-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…Pattern of infection for the different genotypes of HEV, adapted from Centers for Disease Control and Prevention 2020a Pathak and Barde (2017) b Spina et al (2017) c Peron et al (2007) Table 2 Summary of HEV host species by genotype adapted from Kenney (2019) a Infections instigated through experimental conditions Genotype Hosts identified (common names) Species infected Fig. 1 The geographical distribution of HEV genotypes 1-4.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Pattern of infection for the different genotypes of HEV, adapted from Centers for Disease Control and Prevention 2020a Pathak and Barde (2017) b Spina et al (2017) c Peron et al (2007) Table 2 Summary of HEV host species by genotype adapted from Kenney (2019) a Infections instigated through experimental conditions Genotype Hosts identified (common names) Species infected Fig. 1 The geographical distribution of HEV genotypes 1-4.…”
Section: Tablementioning
confidence: 99%
“…Neurological, haematological, immunological and renal manifestations g Older adults (> 40 years) Males 0.5–1% c 4 Yes Foodborne; blood transfusion; organ donation Economically developed and developing countries Unknown Young adults Possibly males (limited data) h 0.5–1% c 5 No Faecal-oral Unknown Unknown Unknown Unknown Unknown 6 No Faecal-oral Unknown Unknown Unknown Unknown Unknown 7 Yes Foodborne; Faecal-oral; blood transfusion? Unknown Unknown Unknown Unknown Unknown 8 No Faecal-oral Unknown Unknown Unknown Unknown Unknown a Pathak and Barde ( 2017 ) b Spina et al ( 2017 ) c Peron et al ( 2007 ) d Kumar et al ( 2017 ) e Jin et al ( 2016 ) f Kamar et al ( 2014 ) g Horvatits et al ( 2019 ) h Mizuo et al ( 2005 ) …”
Section: Introductionmentioning
confidence: 99%
“…Our findings indicate that both the IgM capture ELI-SAs used in MCL and the NL performed equally well in detecting IgM antibodies from patient samples, and IgM ELISA is a good tool for diagnosis of HEV [5,8]. However, IgM ELISA failed to perform accurately on hemolyzed samples, resulting in false-negative results [11].…”
Section: Resultsmentioning
confidence: 99%
“…India is endemic for HEV and outbreak have been documented from India since 1955 [4]. Our studies from central India show that HEV is endemic and perennial transmission occurs with a spike in HEV cases in summer and the post monsoon period [5]. Recently, an outbreak was also documented from central India [6].…”
Section: Introductionmentioning
confidence: 97%
“…Data on risk factors for HEV infection (defined by IgM antibodies or RNA), disease, and death were identified in 36 studies (17,21,26,30,34,46,63,68,74,85,91,92,102,104,(108)(109)(110)112,116,129,138,139,(145)(146)(147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158) from 13 countries between 1990 and 2017. One study only reported risk factors with an unknown hypothesized direction of effect and was excluded from further analysis (159).…”
Section: Risk Factorsmentioning
confidence: 99%